Explicit teaching and authenticity in L2 listening instruction: University language teachers' beliefs. (February 2019) - Emerick, Mark R.
Abstract: The purpose of this study is to understand university language teachers' beliefs about explicit teaching and authentic materials in second language (L2) listening instruction. Data were collected from language teachers in Spanish and English departments at eight universities in Pennsylvania, United States, through an online questionnaire (N = 60) and semi-structured interviews (N = 6). The results indicated that teachers believe explicit listening instruction is essential for learners to develop competence in L2 listening, but conflate direct strategy instruction, listening practice, and listening assessment. Furthermore, very few reported the implementation of metacognitive strategy instruction. Secondly, most instructors believe that authenticity is a valuable construct for L2 teaching; however, generally instructors considered either linguistic features of the listening text or features of the L2 learning context when selecting materials, not both, illustrating differing conceptualizations of authenticity and varied approaches to authentic material selection. These results imply a need for more attention to listening pedagogy in L2 teaching environments and teacher training, especially with regard to explicit strategy and metacognitive instruction and the selection and use of authentic listening texts.